2011
DOI: 10.5334/pb-51-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Learning a Motor Skill: Effects of Blocked Versus Random Practice a Review

Abstract: Procedural learning refers to the ability to learn new perceptual, motor or cognitive skills. While many studies have explored procedural learning abilities in patients with different types of brain damage, the cognitive mechanisms involved in the acquisition of a new skill are still not well understood. The present review focuses on the conditions that optimise skill acquisition, and more specifically on the contextual interference effect (CIE), which refers to the advantage of a 'random' over a 'blocked' pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 129 publications
0
55
1
1
Order By: Relevance
“…However, on retention and transfer tests, the random practice group had a signifi cantly faster total movement time compared to the blocked group, indicating superior learning and the Cl effect (31). The Cl effect has been replicated in many studies examining motor skill tasks across various contexts, as described in several re view articles (20,25,28).Two main theories have been forwarded to explain the Cl effect. First, the reconstruction hypothesis proposes that a random practice order leads to interference between the tasks being practiced, causing them to be forgotten in the short term between trials.…”
mentioning
confidence: 93%
“…However, on retention and transfer tests, the random practice group had a signifi cantly faster total movement time compared to the blocked group, indicating superior learning and the Cl effect (31). The Cl effect has been replicated in many studies examining motor skill tasks across various contexts, as described in several re view articles (20,25,28).Two main theories have been forwarded to explain the Cl effect. First, the reconstruction hypothesis proposes that a random practice order leads to interference between the tasks being practiced, causing them to be forgotten in the short term between trials.…”
mentioning
confidence: 93%
“…Previous research suggests, that complex tasks might cause overload in participants, when paired with demand-enhancing CI (Merbah & Meulemans, 2011;Wulf & Shea, 2002). Thus, in the present study we investigated the effects of CI and inductive reasoning ability in a motor learning task, to test whether reasoning abilities modulate skill acquisition and CI effects.…”
Section: Discussionmentioning
confidence: 98%
“…Despite a comparatively large sample and extensive training across 315 trials, we found no significant main effects of CI in our study, neither in training, nor retention and transfer. Merbah and Meulemans (2011) pointed out that CI in complex tasks is beneficial if the task affords parameter adaptation instead of requiring multiple motor programs. Parameter adaptation is considered to be easier than multiple motor program learning, which may be disrupted by CI due to accumulating task demands.…”
Section: Implications/limitationsmentioning
confidence: 98%
See 2 more Smart Citations